Metabolic Health and Reproductive Performance of Crossbred Cows Fed Varying Levels of Conjugated Linoleic Acid (CLA) during Transition Period - J.S. Sidhu; R.S. Grewal; J.S. Lamba; C. Singh; A.P.S Sethi; Prahlad Singh (Indian Journal of Animal Nutrition, 2023)
Conjugated linoleic acid (CLA) has been shown to influence a range of biological processes. The current study was aimed at evaluating the effect of CLA supplementation during the transition period on blood metabolites and reproductive performance in crossbred cows. Multiparous crossbred cows (n = 30) were allotted to three treatment groups: The control group (CG) was supplemented with 50 g of bypass fat top dressed on a basal diet; the CLA-25 group was supplemented with 25 g of CLA and 25 g of bypass fat top dressed on a basal diet; and the CLA-50 group was supplemented with 50 g of CLA top dressed on a basal diet. Supplementation started -21d from calving and continued until 60 days in milk (DIM). Blood samples were drawn from cows by puncturing the jugular vein at different intervals during the feeding trial (-21d prepartum, -10 d prepartum, 10 d postpartum, and 60 d postpartum) and analysed for blood metabolites. Post-calving concentrations of non-esterified fatty acids (NEFA), beta-hydroxybutyrate (BHBA), and insulin-like growth factor-I (IGF-I) were also analysed. Reproductive parameters like days to first oestrous and days to pregnancy were also recorded. No adverse effect of CLA supplementation on blood metabolites was observed. A positive effect of CLA supplementation on the levels of IGF-I was observed where CLA-supplemented animals had higher values for post-calving IGF-I concentrations. Moreover, CLA supplementation had a significant effect on reproductive parameters where CLA supplemented cows had lower days to first oestrus and days to pregnancy as compared to cows in the control group.